2019
DOI: 10.1080/00207284.2019.1677469
|View full text |Cite
|
Sign up to set email alerts
|

Más Allá De Las Barreras: Competency and Practice Considerations in Language, Cultural, and Social Issues When Delivering Group CPT to Hispanic Immigrants

Abstract: High rates of under-assessed trauma and psychiatric disorders, particularly posttraumatic stress disorder (PTSD) have been reported among Hispanic immigrants, especially as related to immigration trauma. Multiple studies have shown group cognitive processing therapy (CPT) to be an effective evidence-based practice (EBP) for treatment of PTSD across a number of clinical populations. To date, however, no studies have examined important competency and practice issues in linguistic, cultural, and ethical areas tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 83 publications
0
3
0
1
Order By: Relevance
“…While a large degree of heterogeneity exists among the Latinx populations residing in the United States (U.S.), prior work has consistently documented that Latinx individuals are more likely to encounter a myriad of barriers in accessing mental health treatment, which include language, transportation, cost, and stigma surrounding mental illness (Aguilar-Gaxiola et al, 2012; Benuto et al, 2019; Berdahl & Torres Stone, 2009; Bernal & Sáez-Santiago, 2006; Bridges et al, 2012; Kaltman et al, 2016; Sanchez et al, 2016). Such barriers are compounded by disparities in traumatic event exposure (Andrews et al, 2015; Vásquez et al, 2020), suggesting that novel interventions that can improve access to PTSD treatment are of significant need.…”
Section: Ptsd Treatment and Barriers Among Latinx Immigrantsmentioning
confidence: 99%
“…While a large degree of heterogeneity exists among the Latinx populations residing in the United States (U.S.), prior work has consistently documented that Latinx individuals are more likely to encounter a myriad of barriers in accessing mental health treatment, which include language, transportation, cost, and stigma surrounding mental illness (Aguilar-Gaxiola et al, 2012; Benuto et al, 2019; Berdahl & Torres Stone, 2009; Bernal & Sáez-Santiago, 2006; Bridges et al, 2012; Kaltman et al, 2016; Sanchez et al, 2016). Such barriers are compounded by disparities in traumatic event exposure (Andrews et al, 2015; Vásquez et al, 2020), suggesting that novel interventions that can improve access to PTSD treatment are of significant need.…”
Section: Ptsd Treatment and Barriers Among Latinx Immigrantsmentioning
confidence: 99%
“…Latino culture is collectivistic, which is characterised by connectedness, fitting in, meeting other people's expectations, following social norms and caring deeply for those individuals closest to them (Campos & Kim, 2017). This value aligns with PEGs because individuals high in collectivism may quickly learn to value and adapt to the group environment (Torres-Rivera et al, 2014;Vasquez et al, 2020). In a similar way, the cultural value of personalismo emphasises warm, friendly and genuine interactions with other people, which is compatible with the nature of group psychotherapy (Torres-Rivera et al, 2014).…”
Section: Development and Evaluation Of Driven As A Psychoeducational ...mentioning
confidence: 99%
“…Research has also shown that group therapeutic modalities are compatible with Latino values such as collectivism and personalismo (Torres‐Rivera et al., 2014; Vasquez et al., 2020). Latino culture is collectivistic, which is characterised by connectedness, fitting in, meeting other people's expectations, following social norms and caring deeply for those individuals closest to them (Campos & Kim, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Assim, construímos um gatilho para a conscientização quanto a necessidade do autocuidado. Ou seja, se há formas que levam o indivíduo a despertar-se para o referido processo, a mudança de atitude torna-se viável (Vasquez et al, 2020).…”
Section: Percepções Comuns àS Oficinasunclassified